Gender equality in the family and childbearing - Lars Dommermuth; Bryndl Hohmann-Marriott; Trude Lappegård (Statistics Norway, Research Department, 2013)
This study focuses on the possible effect of gender equality and equity in the family on the transition to first, second and third births. The analysis includes the division of housework and childcare as well as the perception of whether this division is fair and just. We use a unique dataset combining data from the Norwegian GGS (2007) with information from population register on subsequent childbirths. Results indicate a varying effect of gender equality in the family on childbearing. An unequal division of housework has a negative effect on first and subsequent births. Couples were men contribute more to housework than women, have lower likelihood of first and second births compared to couples with a more typical division where women do more but men contribute substantially. In the same way, couples where the woman does almost all housework has lower likelihood of a third birth. Even though the division of childcare has no substantial impact on continued childbearing, the perception of this division is relevant for parents with one child. Couples in which the respondent perceives the division of childcare as less equitable are less likely to get a second child.
Keywords: N34; Z10; Z13; 330; Childbearing; Gender equality; Gender equity; Division of housework; Division of childcare